Method for synthesizing titanium-containing mordenite

Titanium is introduced directly in one step through hydrothermal synthesis method of inorganic titanium sources, solving the problems of high preparation costs and low titanium content in the prior art, and achieving low cost and efficient preparation of mordenite molecular sieve, which is suitable for industrial applications.

CN119240729APending Publication Date: 2025-01-03HEBEI MEIBANG ENG & TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411369156.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing preparation methods for titanium-containing mercury zeolite molecular sieve are costly, complex in process, and low in titanium content, making it difficult to achieve large-scale industrial production.

Method used

Titanium is directly introduced into the microporous material framework through hydrothermal synthesis method. By adjusting the addition order and dosage of aluminum, titanium, alkaline and silicon sources, the process is simplified and the titanium content is increased.

Benefits of technology

The preparation of mordenite molecular sieve with low cost, simplified processes and increased titanium content is achieved, reducing production costs, and environmentally friendly processes, suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119240729A_ABST
    Figure CN119240729A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of zeolite molecular sieves, and particularly discloses a preparation method of titanium-containing mordenite. Comprising the following steps: (1) uniformly mixing deionized water, an aluminum source and a titanium source to obtain a component A; uniformly mixing deionized water, an alkali source and a silicon source to obtain a component B; (2) mixing the component A and the component B to obtain a component C; (3) adding a seed crystal into the component C, and uniformly stirring to obtain a gel precursor; (4) putting the gel precursor into a high-pressure reaction kettle for dynamic crystallization; and (5) after crystallization, carrying out solid-liquid separation, washing the obtained solid with water, and drying to obtain the titanium-containing mordenite molecular sieve. According to the method, titanium is directly synthesized on a microporous material framework in one step through a hydrothermal synthesis method, and the method has the advantages of low raw material cost, simple process, short production period and the like, and has a very good industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of zeolite molecular sieves, and in particular to a method for synthesizing titanium-containing mordenite. Background Art

[0002] Mordenite (MOR) is a large-pore molecular sieve with a one-dimensional 12-membered ring channel and an 8-membered ring channel. Due to its long-range structural order and excellent thermal stability, it has become an important catalytic material in petrochemical and coal chemical industries. At the same time, titanium-containing mordenite molecular sieves show excellent catalytic performance in aromatic hydroxylation, olefin epoxidation and ammoximation of ketones.

[0003] Due to the limitation of the pore structure, it is difficult to introduce the most reactive heterometallic atom titanium into the zeolite framework in one step through the hydrothermal synthesis strategy. At present, the main synthesis method of titanium-containing mordenite molecular sieve (Ti-MOR molecular sieve) is to adopt the strategy of post-titanium addition, and to place titanium into the mordenite molecular sieve framework through the gas-solid phase replacement method or the liquid-solid phase replacement method after the dealuminated mordenite. For example, Chinese patent CN100522813C discloses a method for preparing titanium-containing zeolite molecular sieve by modifying natural zeolite, which uses natural zeolite as raw material, undergoes ion exchange, chemical dealuminization treatment, and gas-solid phase replacement reaction to obtain titanium-containing zeolite molecular sieve. However, due to the low purity of natural zeolite, the pores are not regular and blocked, and the mass transfer resistance of the gas-solid phase is large, so it is difficult to prepare mordenite molecular sieve with high titanium content. Chinese patent CN115417420A discloses a method for preparing Ti-MOR molecular sieves, which firstly crystallizes and synthesizes borosilicate aluminum molecular sieves with a MOR structure, and then reacts the borosilicate aluminum molecular sieves with the MOR structure with ammonium fluoride and amorphous titanium dioxide under ultraviolet light after acid washing to obtain Ti-MOR molecular sieves. The preparation process of the Ti-MOR molecular sieve can avoid the use of organic amines and does not require high-temperature vapor phase titanium addition reaction, but the fluorine-containing reaction liquid has high requirements for the device, and the fluorine-containing waste liquid after multiple uses is difficult to handle.

[0004] It is reported in the literature that titanium-containing mordenite molecular sieve can be directly hydrothermally synthesized (Studies in Surface Science and Catalysis, 113, 195-200 (1998)), but it is necessary to use triethylenediamine as a template, which is expensive and cannot be produced on a large scale. Chinese patent CN102674389A provides a method for preparing a nano-mordenite molecular sieve containing Ti, wherein aluminum source and silicon source are stirred and mixed into a gel, mordenite is added as a seed, and finally a small molecule organic amine containing Ti is added to the mixed solution, and after stirring and mixing evenly, after crystallization reaction, a titanium-containing nano-mordenite molecular sieve is prepared. Although the method directly introduces transition metal Ti atoms into the zeolite molecular sieve framework by in-situ hydrothermal synthesis in one step, however, it needs to use small molecule organic amines as chelating agents for heterometallic titanium atoms, and the titanium source adopts organic alcohol salts containing Ti in the preparation process, and the production cost is still high.

[0005] Titanium-containing mordenite molecular sieves have become heteroatom molecular sieves for industrial applications. Therefore, if a preparation method with simple and effective preparation process, low cost and reduced environmental pollution can be developed, it will have higher industrial application value. Summary of the invention

[0006] In view of the problems of high cost, complex process and low titanium content in the existing preparation method of titanium-containing mordenite molecular sieve, the present invention provides a method for synthesizing titanium-containing mordenite. The method directly synthesizes titanium onto the microporous material skeleton in one step by a hydrothermal synthesis method, and the titanium source used is inorganic titanium, which has the advantages of low raw material cost, simple process steps, short production cycle, high product yield, and environmental friendliness.

[0007] To achieve the above object, the present invention adopts the following technical solution: A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, an aluminum source and a titanium source, and stir at room temperature until the solution is uniform and transparent to obtain component A; mix deionized water, an alkali source and a silicon source, and stir at room temperature until the solution is uniform to obtain component B; wherein the aluminum source is an inorganic aluminum salt that is acidic after dissolution, and the titanium source is an inorganic titanium salt that is soluble in an acidic solution; Step 2: Mix component A and component B, and stir vigorously until they are uniform to obtain component C; Step 3: Add seed crystals to component C and continue to stir vigorously until uniform to obtain a gel precursor; Step 4: placing the gel precursor in a high pressure reactor and subjecting it to dynamic crystallization at 160-180°C for 0.5-5 days under stirring conditions; Step 5: After the crystallization is completed, the solid and liquid are separated, and the obtained solid is washed with water until the pH value is ≤ 9, and dried at 95-110° C. for 0.5-2 days to obtain a titanium-containing mordenite molecular sieve.

[0008] Furthermore, in step 1, deionized water, an aluminum source and a titanium source are mixed, and stirred at room temperature for 2 to 5 hours to obtain component A; deionized water, an alkali source and a silicon source are mixed, and stirred at room temperature for 0.5 to 3 hours to obtain component B.

[0009] Furthermore, in step 1, the aluminum source is preferably one or a combination of aluminum nitrate, aluminum chloride, and aluminum sulfate.

[0010] Furthermore, in step 1, the titanium source is preferably one or a combination of titanyl sulfate, titanium sulfate, and titanium trichloride.

[0011] Furthermore, in step 1, the silicon source is one or a combination of water glass, white carbon black, silica sol, C-type silica gel or powdered silica gel.

[0012] Furthermore, in step 1, the alkali source is an alkali metal hydroxide, preferably sodium hydroxide or potassium hydroxide, more preferably sodium hydroxide.

[0013] Furthermore, in step 2, component A and component B are mixed and vigorously stirred for 1 to 3 hours to obtain component C.

[0014] Furthermore, in step 3, seed crystals are added to component C, and vigorous stirring is continued for 0.5 to 3 hours to obtain a gel precursor.

[0015] Furthermore, in step 3, the seed crystal is mordenite.

[0016] Furthermore, in step 3, the solid content of the gel precursor is 5-20%, and the components thereof, in terms of molar ratio, are SiO2:Al2O3:TiO2:Na2O:H2O of 1:(0.02-0.2):(0.01-0.1):(0.2-0.8):(10-50), and the amount of seed crystal added is 0.5-10% of the mass of the silicon source.

[0017] Furthermore, in step 3, a template may be added while adding the seed crystals, and then vigorously stirred for 0.5 to 3 hours until uniform, to obtain a gel precursor; The template agent is a tetraethyl organic ammonium salt template agent, preferably one or a combination of tetraethylammonium hydroxide, tetraethylammonium bromide, and tetraethylammonium hydrogen sulfate; The components of the gel precursor are SiO2: Al2O3: TiO2: Na2O: TEA2O: H2O in a molar ratio of 1: (0.02-0.2): (0.01-0.1): (0.2-0.8): (0-0.5): (10-50), and the amount of seed crystal added is 0.5-10% of the mass of the silicon source.

[0018] Furthermore, in step 4, during the dynamic crystallization process, the stirring speed is 10-1000 rpm, and the pressure in the high-pressure reactor is 0.5-1.0 MPa.

[0019] Compared with the prior art, the beneficial effects of the present invention are: In the method of the present invention, when both the aluminum source and the titanium source are inorganic materials, the addition sequence and dosage of the aluminum source, the titanium source, the alkali source and the silicon source are adjusted, so that titanium is directly synthesized into the microporous material skeleton in one step through hydrothermal synthesis, which not only avoids secondary titanium supplementation, simplifies the preparation process, shortens the production cycle, but also avoids the use of expensive organic aluminum and organic titanium, greatly reduces the cost of raw materials, and the obtained mordenite molecular sieve has a high titanium content and has a good industrial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 1 is the X-ray powder diffraction (XRD) pattern of the titanium-containing mordenite described in Examples 1-8.

[0021] Figure 2 This is the UV-Visible absorption spectrum of the titanium-containing mordenite described in Examples 1-8.

[0022] Figure 3 It is the ultraviolet-visible absorption (UV-Visible) spectrum of the titanium-containing mordenite described in Comparative Examples 1, 2, and 4. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] Example 1 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, aluminum sulfate and titanyl sulfate, and stir at room temperature for 2 hours until the solution is transparent to prepare component A; mix deionized water, water glass and sodium hydroxide, and stir at room temperature for 1 hour until the mixture is uniform to prepare component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2:Al2O3:TiO2:Na2O:H2O = 1:0.1:0.025:0.4:25, and the amount of seed added is 5% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization growth at 175°C for 36 hours under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH value is ≤ 9, and dried at 100° C. for 12 hours to obtain a dry solid product.

[0025] The component content of the dried solid product was tested by X-ray fluorescence spectrometer (XRF), and it was found that Na2O was 6.3304%, Al2O3 was 9.0327%, TiO2 was 2.9203%, and SiO2 was 79.93%.

[0026] The specific surface area of ​​the dry solid product was analyzed by BET specific surface and pore size analyzer, and the specific surface area was 523.372 m 2 / g.

[0027] The phase structure and crystallinity of the dried solid product were detected by X-ray diffractometer (XRD). The XRD characterization results are as follows: Figure 1 As shown, it is shown that the dry solid product has a mordenite crystal structure.

[0028] The coordination state of titanium in the molecular sieve framework of the dry solid product was detected by UV-Vis spectrometer. The UV-Vis characterization results are as follows: Figure 2 As shown, combined with the XRF results, it shows that most of the Ti is incorporated into the molecular sieve framework rather than being free and non-framework titanium.

[0029] Example 2 Step 1: Mix deionized water, aluminum chloride and titanium trichloride, and stir at room temperature for 2 hours until the solution becomes transparent to prepare component A; mix deionized water, water glass and potassium hydroxide, and stir at room temperature for 1 hour until the mixture is uniform to prepare component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2:Al2O3:TiO2:Na2O:H2O = 1:0.15:0.08:0.45:15, and the amount of seed added is 2% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization growth at 175°C for 2 days under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH value is ≤ 9, and dried at 100° C. for 12 hours to obtain a dry solid product.

[0030] The component content of the dried solid product was tested by X-ray fluorescence spectrometer (XRF), and it was found that Na2O was 8.3239%, Al2O3 was 11.9195%, TiO2 was 9.1282%, and SiO2 was 69.02%.

[0031] The specific surface area of ​​the dry solid product was analyzed by BET specific surface and pore size analyzer, and its specific surface area was 423.403 m 2 / g.

[0032] The phase structure and crystallinity of the dried solid product were detected by X-ray diffractometer (XRD). The XRD characterization results are as follows: Figure 1 As shown, it is shown that the dry solid product has a mordenite crystal structure.

[0033] The coordination state of titanium in the molecular sieve framework of the dry solid product was detected by UV-Vis spectrometer. The UV-Vis characterization results are as follows: Figure 2 As shown, combined with the XRF results, it shows that most of the Ti is incorporated into the molecular sieve framework rather than being free and non-framework titanium.

[0034] Example 3 Step 1: Mix deionized water, aluminum nitrate and titanium sulfate, and stir at room temperature for 2 hours until the solution is transparent to prepare component A; mix deionized water, water glass and potassium hydroxide, and stir at room temperature for 1 hour until the solution is uniform to prepare component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and tetraethylammonium bromide at the same time, and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2:Al2O3:TiO2:Na2O:TEA2O:H2O = 1:0.025:0.025:0.25:0.5:50, and the amount of seed added is 10% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization growth at 175°C for 3 days under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH value is ≤ 9, and dried at 100° C. for 0.5 days to obtain a dry solid product.

[0035] The component content of the dried solid product was tested by X-ray fluorescence spectrometer (XRF), and it was found that Na2O was 2.3196%, Al2O3 was 2.8625%, TiO2 was 3.2572%, and SiO2 was 89.77%.

[0036] The specific surface area of ​​the dried solid product was analyzed by BET specific surface and pore size analyzer, and the specific surface area was 430.443 m 2 / g.

[0037] The phase structure and crystallinity of the dried solid product were detected by X-ray diffractometer (XRD). The XRD characterization results are as follows: Figure 1 As shown, it is shown that the dry solid product has a mordenite crystal structure.

[0038] The coordination state of titanium in the molecular sieve framework of the dry solid product was detected by UV-Vis spectrometer. The UV-Vis characterization results are as follows: Figure 2 As shown, combined with the XRF results, it shows that most of the Ti is incorporated into the molecular sieve framework rather than being free and non-framework titanium.

[0039] Embodiments 4 to 8 The implementation process is the same as Example 1 except for the following differences.

[0040] Example 4 Step 3: Add tetraethylammonium hydroxide as a template while adding the seed crystals; at the same time, adjust the ratio of the gel precursor, in terms of molar ratio SiO2:Al2O3:TiO2:Na2O:TEA2O:H2O = 1:0.04:0.04:0.35:0.04:15.

[0041] The dried solid product was tested by XRF and its components were Na2O 5.8761%, Al2O3 6.1731%, TiO2 5.6187%, and SiO2 80.61%. The specific surface area of ​​the product was 432.216 m 2 / g, XRD pattern and Figure 1 Consistent, UV-Vis and Figure 2 Consistent.

[0042] Example 5 Step 3: Add tetraethylammonium hydrogen sulfate as a template while adding the seed crystal; at the same time, adjust the ratio of the gel precursor, in terms of molar ratio SiO2:Al2O3:TiO2:Na2O:TEA2O:H2O = 1:0.04:0.04:0.4:0.08:25.

[0043] The dried solid product was tested by XRF and its components were Na2O 7.0706%, Al2O3 7.0233%, TiO2 5.0865%, and SiO2 77.96%. The specific surface area of ​​the product was 451.753 m 2 / g, XRD pattern and Figure 1 Consistent, UV-Vis and Figure 2 Consistent.

[0044] Example 6 In step 1, silica sol is used instead of water glass.

[0045] The dried solid product was tested by XRF and its components were Na2O 6.1212%, Al2O3 8.8671%, TiO2 3.1326%, and SiO2 80.36%. The specific surface area of ​​the product was 482.930 m 2 / g, XRD pattern and Figure 1 Consistent, UV-Vis and Figure 2 Consistent.

[0046] Example 7 In step 1, silica sol is used instead of water glass; and in step 3, tetraethylammonium hydroxide is added as a template while adding the seed crystal, and the ratio of the gel precursor is adjusted at the same time, and the molar ratio of SiO2:Al2O3:TiO2:Na2O:TEA2O:H2O = 1:0.04:0.04:0.4:0.04:25.

[0047] The dried solid product was tested by XRF and its components were Na2O 6.9631%, Al2O3 6.1522%, TiO2 5.4875%, and SiO2 79.29%. The specific surface area of ​​the product was 443.572 m 2 / g, XRD pattern and Figure 1Consistent, UV-Vis Figure 2 Consistent.

[0048] Example 8 In step 1, white carbon black is used instead of water glass; and in step 3, tetraethylammonium hydroxide is added as a template while adding the seed crystal, and the ratio of the gel precursor is adjusted at the same time, and the molar ratio of SiO2:Al2O3:TiO2:Na2O:TEA2O:H2O is 1:0.05:0.025:0.35:0.025:35.

[0049] The dried solid product was tested by XRF and its components were Na2O 5.8305%, Al2O3 8.3944%, TiO2 3.1945%, and SiO2 81.01%. The specific surface area of ​​the product was 531.330 m 2 / g, XRD pattern and Figure 1 Consistent, UV-Vis and Figure 2 Consistent.

[0050] Comparative Example 1 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, aluminum sulfate, titanyl sulfate, water glass and sodium hydroxide, and stir at room temperature for 2 hours to prepare a uniform component A; Step 2: Add seed mordenite to component A and continue to stir vigorously for 1 hour until uniform to obtain a gel precursor; The gel precursor has a molar ratio of SiO2:Al2O3:TiO2:Na2O:H2O = 1:0.05:0.025:0.35:25, and the amount of seed added is 5% of the weight of SiO2; Step 3: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization at 175°C for 36 hours under stirring conditions of 10-1000 rpm; Step 4: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH is ≤ 9, and dried at 100° C. for 12 h to obtain a dry solid product.

[0051] The crystal structure of the dried solid product was detected by X-ray diffractometer (XRD), and it was found that the synthesized mordenite molecular sieve had low crystallinity. The specific surface area of ​​the mordenite molecular sieve was 221.107 m 2 / g. The results are as follows: Figure 3 As shown, it can be seen that most of the titanium is extra-framework anatase.

[0052] Comparative Example 2 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water and titanyl sulfate, and stir at room temperature for 2 hours until the solution becomes transparent to prepare component A; Deionized water, aluminum sulfate, water glass and sodium hydroxide were mixed and stirred at room temperature for 1 hour until uniform, thereby preparing component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2: Al2O3: TiO2: Na2O: H2O = 1: 0.05: 0.025: 0.35: 25, and the amount of seed crystal added is 5% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization at 175°C for 36 hours under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH is ≤ 9, and dried at 100° C. for 12 h to obtain a dry solid product.

[0053] The crystal structure of the dried solid product was detected by X-ray diffractometer (XRD), and it was found that the synthesized mordenite molecular sieve had low crystallinity. The specific surface area of ​​the mordenite molecular sieve was 282.352 m 2 / g. The results are as follows: Figure 3 As shown, it can be seen that most of the titanium is extra-framework anatase.

[0054] Comparative Example 3 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, aluminum sulfate and titanyl sulfate, stir at room temperature for 2 hours until the solution is transparent, add seed mordenite to the transparent solution and continue to stir vigorously for 1 hour to prepare component A; Step 2: Mix deionized water, water glass and sodium hydroxide, stir at room temperature for 1 hour, and stir evenly to prepare component B; Step 3: Mix component A and component B, and stir vigorously for 1 hour until they are uniform to obtain a gel precursor; The gel precursor has a molar ratio of SiO2: Al2O3: TiO2: Na2O: H2O = 1: 0.05: 0.025: 0.35: 25, and the amount of seed crystal added is 5% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization at 175°C for 36 hours under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH is ≤ 9, and dried at 100° C. for 12 h to obtain a dry solid product.

[0055] The crystal structure of the dried solid product was detected by X-ray diffractometer (XRD), and it was found that the crystallinity of the synthesized mordenite molecular sieve was close to that of the mordenite molecular sieve. The specific surface area of ​​the mordenite molecular sieve was 403.251 m 2 / g. Through UV-Visible spectrometer detection, most of the titanium is in the zeolite framework.

[0056] Comparative Example 4 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, aluminum sulfate, titanyl sulfate and sodium hydroxide, and stir at room temperature for 2 hours until the solution is transparent to prepare component A; Mix deionized water and water glass, stir at room temperature for 1 hour, and stir evenly to prepare component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2: Al2O3: TiO2: Na2O: H2O = 1: 0.05: 0.025: 0.35: 25, and the amount of seed crystal added is 5% of the weight of SiO2; Step 4: Place the gel precursor in a high pressure reactor with a pressure of 0.5-1.0 MPa and perform dynamic crystallization at 175°C for 36 hours under stirring conditions of 10-1000 rpm; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH is ≤ 9, and dried at 100° C. for 12 h to obtain a dry solid product.

[0057] The crystal structure of the dried solid product was detected by X-ray diffractometer (XRD), and it was found that the synthesized mordenite molecular sieve had low crystallinity. The specific surface area of ​​the mordenite molecular sieve was 201.407 m 2 / g. The results are as follows: Figure 3 As shown, it can be seen that most of the titanium is extra-framework anatase.

[0058] Comparative Example 5 A method for synthesizing titanium-containing mordenite comprises the following process steps: Step 1: Mix deionized water, aluminum sulfate and titanyl sulfate, and stir at room temperature for 2 hours until the solution is transparent to prepare component A; Deionized water, water glass and sodium hydroxide were mixed and stirred at room temperature for 1 hour until uniform, thereby preparing component B; Step 2: Mix component A and component B, and stir vigorously for 1 hour until they are uniform, to prepare component C; Step 3: Add seed mordenite to component C and continue to stir vigorously for 1 hour until uniform, to obtain a gel precursor; The gel precursor has a molar ratio of SiO2: Al2O3: TiO2: Na2O: H2O = 1: 0.05: 0.025: 0.35: 25, and the amount of seed crystal added is 5% of the weight of SiO2; Step 4: Place the gel precursor in a static reactor and crystallize at 175°C for 36 hours; Step 5: After the crystallization is completed, the solid-liquid separation is performed, and the obtained solid is washed with water until the pH is ≤ 9, and dried at 100° C. for 12 h to obtain a dry solid product.

[0059] The crystal structure of the dried solid product was detected by X-ray diffractometer (XRD), and it was found that the crystallinity of the synthesized mordenite molecular sieve was low. The specific surface area of ​​386.535 m 2 / g. Through UV-Visible spectrometer detection, most of the titanium is in the zeolite framework.

[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for synthesizing titanium-containing mordenite, characterized in that: The following steps are involved: Step 1: Mix deionized water, an aluminum source and a titanium source, and stir at room temperature until the solution is uniform and transparent to obtain component A; mix deionized water, an alkali source and a silicon source, and stir at room temperature until the solution is uniform to obtain component B; wherein the aluminum source is an inorganic aluminum salt that is acidic after dissolution; and the titanium source is an inorganic titanium salt that is soluble in an acidic solution; Step 2: Mix component A and component B, and stir vigorously until they are uniform to obtain component C; Step 3: Add seed crystals to component C and continue to stir vigorously until uniform to obtain a gel precursor; Step 4: placing the gel precursor in a high pressure reactor and subjecting it to dynamic crystallization at 160-180°C for 0.5-5 days under stirring conditions; Step 5: After the crystallization is completed, the solid and liquid are separated, and the obtained solid is washed with water until the pH value is ≤ 9, and dried at 95-110° C. for 0.5-2 days to obtain a titanium-containing mordenite molecular sieve.

2. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: In step 1, the alkali source is an alkali metal hydroxide; the silicon source is one or a combination of water glass, white carbon black, silica sol, C-type silica gel or powdered silica gel.

3. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: The aluminum source is one or a combination of aluminum nitrate, aluminum chloride, and aluminum sulfate; the titanium source is one or a combination of titanyl sulfate, titanium sulfate, and titanium trichloride.

4. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: In step 3, the seed crystal is mordenite.

5. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: In step 3, the components of the gel precursor are SiO2:Al2O3:TiO2:Na2O:H2O in a molar ratio of 1:(0.02-0.2):(0.01-0.1):(0.2-0.8):(10-50), and the amount of seed crystal added is 0.5-10% of the mass of the silicon source.

6. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: In step 3, the template is added at the same time as the seed crystal, and then vigorously stirred until uniform to obtain a gel precursor.

7. The method for synthesizing titanium-containing mordenite according to claim 6, characterized in that: The template agent is a tetraethyl organic ammonium salt template agent.

8. The method for synthesizing titanium-containing mordenite according to claim 7, characterized in that: The template agent is one or a combination of tetraethylammonium hydroxide, tetraethylammonium bromide and tetraethylammonium hydrogen sulfate.

9. The method for synthesizing titanium-containing mordenite according to claim 6, characterized in that: The components of the gel precursor are SiO2: Al2O3: TiO2: Na2O: TEA2O: H2O in a molar ratio of 1: (0.02-0.2): (0.01-0.1): (0.2-0.8): (0-0.5): (10-50), and the amount of seed crystal added is 0.5 to 10% of the mass of the silicon source.

10. The method for synthesizing titanium-containing mordenite according to claim 1, characterized in that: In step 4, during the dynamic crystallization process, the stirring speed is 10-1000 rpm, and the pressure in the high-pressure reactor is 0.5-1.0 MPa.